Potential unlocked: Art in prison. Issue 1 (1st July 2018) - Carpenter, Benedict; Knight, Victoria
This article introduces a three-year project begun in 2018 that investigates the relationship between visual arts education and mental health recovery for prisoners and probationers. The project is delivered in custodial contexts in Leicester, UK. The research engages young offenders with mental health conditions in creating visual artwork for public exhibition and publication. Insight into mental health recovery is gained through semi-structured interviews with participants. Participant well-being is coded through the CHIME framework. Some early findings are that the workshops help to alleviate the deep boredom of prison life; they are a useful distraction and an opportunity for introspection; they promote future thinking; and they help prisoners to connect with families. The research is aligned with the UN Sustainable Development Goal 3: Good health and wellbeing; and Goal 16: Promote peaceful and inclusive societies for sustainable development.